Z dziejów prasy łódzkiej. „Kurier Łódzki” i „Echo” - wydawnictwa Jana Stypułkowskiego (1919-1939) - Olejnik, Leszek (Acta Universitatis Lodziensis. Folia Historica, 1995)
In this article the history of one of two biggest Lodz publishing houses in the 2nd Rzeczpospolita (Republic) was presented. The lawyer Jan Stypulkowski played the main role in it, although at first he had a few partners (1920-1923 cx-Primc Minister Leopold Skulski). Since December 1919 the company edited „Kurier Łódzki” newspaper which arose on the base of the paper of the same title, bought from the previous publisher - Stanisław Książek - and of „Straż Polska”. In 1925 Jan Stypulkowski started publishing his sensational afternoon paper „Łódzkie Echo Wieczorne” (1928-1939 - „Echo”). In the early 1930’s on the intersection of 195 Piotrkowska Street and 2 Żwirki Street a modem building, containing a printing firm and offices of both newspapers, was built. In the 1930’s basing on many local mutations of „Echo” the newspaper company owned by Jan Stypułkowski successfully competed for the readers’ market on almost the whole teritory of Poland. The newspapers of the discussed above company underwent in the interwar period a significant ideological and political evolution. Until 1922 „Kurier Łódzki” was connected with the National Peasants’ Union and then it represented the Christian-Democratic direction. From the close of the 1920’s both newspapers gradually passed on to pro-sanacional positions.